Pulmonary Exacerbations in Pediatric Patients: Retrospective Study in a Portuguese Cystic Fibrosis Center - Rosa Cardoso; Ana Lúcia Cardoso; Telma Barbosa (MDPI AG, 2022)
(1) Background: Cystic fibrosis (CF) is a multisystemic disease caused by mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) gene. Lung disease, the leading cause of morbimortality, is marked by acute worsening of symptoms-such as pulmonary exacerbations (PEx). The objectives of this study were: Identifying the frequency of PEx in pediatric CF patients; Characterizing each PEx; Finding association between the frequency and characteristics of the PEx and patients' features. (2) Methods: Retrospective analysis of all PEx from a period of January 2015 to December 2019 in a group of pediatric patients from a single CF center. Data were collected from medical records. Descriptive statistics and chi-square/Fisher's test were used. (3) Results: Thirty-four pediatric patients contributed to the total sample used in this study and 198 PEx were identified, median of 1.0 PEx/patient/year. Most frequent PEx symptoms were increased cough (93.9%) and change in secretions (88.4%), most common pathogens were Staphylococcus aureus (54.9%) and Pseudomonas aeruginosa (24.9%). The majority were treated as outpatient (85.9%). Most common antibiotics included amoxicillin/clavulanate (35.9%) and ciprofloxacin (22.7%). Outcome was favorable in all PEx. (4) Conclusion: Results were consistent with what has been described in literature. More studies are necessary for a better characterization of CF PEx, in order to develop standardized protocols for their management.